Structural analysis of 3D printed UAV - Ong, Dinar Tirta Suraja (2017)
Research on Unmanned Aerial Vehicles (UAV) has been growing recently. A lot of these researches focus on increasing the endurance of the UAV, meaning increasing flight time. Increase in endurance can be achieved by making the UAV design more efficient aerodynamically (good lift and drag performance) and structurally (light). Designing efficient UAV structure has always been limited by manufacturability. Conventionally, it is usually very hard to create a favorable structure, for instance creating elliptic wing. However, with the advancement in advanced manufacturing (AM) technology, such as 3D printing, creating favorable design is more possible and easier. The advancement of topology optimization method can also synergize well with AM technology to create more efficient structure to improve performance of UAV. In this report, the author would like to make use of the combination of these technologies in order to design an effective structure for a flying wing UAV. Technologies that would be used in this study include 3D printing, fiber printing, topology optimization and finite element simulation. The methodology proposed is to use theoretical formula to create general preliminary design, topology optimization to refine the design, varying 3D printing infill setting to achieve the desired structure weight and structural simulation to investigate the performance of the structure.